Perlindungan Hukum Terhadap Perempuan Korban Kekerasan Seksual Dengan Relasi Kuasa - Suci Amelia Putri; Yenny Fitri Z (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
Women have long been frequent targets of sexual violence. In society, This study examines the legal protection for women who experience sexual violence in power relations, with a focus on the normative development of Indonesian law. Sexual violence in power relations occurs when perpetrators exploit structural, social, or institutional authority to dominate victims, particularly in educational and professional settings. Using a normative juridical method, this research analyzes statutory regulations, legal theories, and scholarly opinions—primarily the Indonesian Law No. 12 of 2022 on Sexual Violence Crimes (TPKS) and Permendikbud No. 30 of 2021. The findings show that Indonesian legal reform has shifted from a limited KUHP-based definition toward a victim-centered and restorative justice approach. However, implementation challenges remain, especially regarding enforcement, institutional accountability, and protection against retaliation. This study emphasizes the necessity of strengthening survivor-centered mechanisms and legal awareness to prevent repeated abuse of power within academic and institutional environments.